2009
DOI: 10.1002/mc.20560
|View full text |Cite
|
Sign up to set email alerts
|

Inositol hexaphosphate downregulates both constitutive and ligand-induced mitogenic and cell survival signaling, and causes caspase-mediated apoptotic death of human prostate carcinoma PC-3 cells

Abstract: Constitutively active mitogenic and pro-survival signaling cascades due to aberrant expression and interaction of growth factors and their receptors are well documented in human prostate cancer (PCa). EGF and IGF-1 are potent mitogens that regulate proliferation and survival of PCa cells via autocrine and paracrine loops involving both MAPK- and Akt-mediated signaling. Accordingly, here we assessed the effect of inositol hexaphosphate (IP6) on constitutive and ligand (EGF and IGF-1)-induced biological response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…At 60% confluency, cells were serum starved (SS) for 24 h, treated with 100 μM silibinin and after 2 h, stimulated with EGF or IGF1 (50 ng/mL), and harvested as described previously. 47 In experiments, using inhibitors like antioxidants, PD98059, and 3MA, cells were pretreated with inhibitors for 2 h followed by silibinin treatment. For autophagic flux determination, lysosomal inhibitors: E64d and pepstatin A were added to the media with silibinin and incubated for respective time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 60% confluency, cells were serum starved (SS) for 24 h, treated with 100 μM silibinin and after 2 h, stimulated with EGF or IGF1 (50 ng/mL), and harvested as described previously. 47 In experiments, using inhibitors like antioxidants, PD98059, and 3MA, cells were pretreated with inhibitors for 2 h followed by silibinin treatment. For autophagic flux determination, lysosomal inhibitors: E64d and pepstatin A were added to the media with silibinin and incubated for respective time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Trypan blue dye-exclusion and/or MTT assay was used to assess cell viability. 47 For in vitro clonal analysis, single cells were plated at a density of 1000 cells/well in a six well plate and cultured for 1 week in media under serum conditions with or without silibinin, which was then replenished after every 72 h. Number of cells/ individual clones was counted at experiment end, and clones cells display redox vulnerability which on exposure to silibinin causes them to generate more oxidative stress so as to compromise cellular viability. We do realize that more mechanistic studies need to be performed in the future to determine the mechanism associated with the differential response of CRC cells and normal colon cells to silibinin.…”
Section: Discussionmentioning
confidence: 99%
“…Both myo-Ins and InsP 6 have been also proven to be effective as safe chemopreventive agents, by triggering anti-oxidant and anti-inflammatory effects [93]. Namely, it has been demonstrated that InsP 6 inhibits IGF-1 receptor (IGF-1R) pathway-mediated sustained growth in cancer [94]. Given that myo-Ins may efficiently counteract insulin resistance (IR), it is tempting to speculate that it may also prevent IGF-1 increase associated to IR.…”
Section: Cancermentioning
confidence: 99%
“…ERK1/2 is a survival moderator, however sustained ERK1/2 activation might also induce cell death [11]. The activation of JNK1/2 and p38 are generally implicated in the induction of cell death and inflammation after exposure to stress conditions [15]. MAPKs are also known to mediate apoptosis via activation of caspases [16].…”
Section: Introductionmentioning
confidence: 99%